Improved Fracture Healing in Patients with Concomitant Traumatic Brain Injury: Proven or Not? - Martijn Hofman; Guido Koopmans; Philipp Kobbe; Martijn Poeze; Hagen Andruszkow; Peter R. G. Brink; Hans-Christoph Pape (Mediators of Inflammation)
Over the last 3 decades, scientific evidence advocates an association between traumatic brain injury (TBI) and accelerated fracture healing. Multiple clinical and preclinical studies have shown an enhanced callus formation and an increased callus volume in patients, respectively, rats with concomitant TBI. Over time, different substances (cytokines, hormones, etc.) were in focus to elucidate the relationship between TBI and fracture healing. Until now, the mechanism behind this relationship is not fully clarified and a consensus on which substance plays the key role could not be attained in the literature. In this review, we will give an overview of current concepts and opinions on this topic published in the last decade and both clinical and pathophysiological theories will be discussed.